1996
DOI: 10.3168/jds.s0022-0302(96)76368-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freezing on the Viability of Nine Pathogens from Quarters with Subclinical Mastitis

Abstract: Milk samples from 45 quarters containing mastitis pathogens were collected from lactating cows to determine the viability of those pathogens after freezing. An initial bacteria count was conducted, and samples were divided into 2-ml portions and frozen. Weekly bacteria counts were conducted for 6 wk. Viability after freezing was determined on five isolates of nine bacterial species: Staphylococcus aureus, Staphylococcus hyicus, Staphylococcus chromogenes, Staphylococcus xylosus, Streptococcus agalactiae, Strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 4 publications
5
30
0
1
Order By: Relevance
“…TNase was confirmed to retain its 100% activity at these temperatures as was expected due to its thermal stability. These results are also consistent with other reports, that freezing of quarter milk samples for 6 weeks did not effect the viability of nine pathogens including S. aureus [19].…”
Section: Resultssupporting
confidence: 83%
“…TNase was confirmed to retain its 100% activity at these temperatures as was expected due to its thermal stability. These results are also consistent with other reports, that freezing of quarter milk samples for 6 weeks did not effect the viability of nine pathogens including S. aureus [19].…”
Section: Resultssupporting
confidence: 83%
“…aureus isolation. Murdough et al (1996) and McDougall (1999) found that pre-culture freezing at -20 8C had no effect on the viability of a range of bacterial species isolated from subclinically affected bovine and caprine milk samples. Schukken et al (1989) found that that pre-culture freezing at -20 8C, and increased duration of freezing, decreased the number of bovine milk samples from which Esch.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown that freezing has no effect on Staphylococcus aureus (Luedecke et al 1972;Murdough et al 1996). Several studies have determined that there is a significant decrease in the number of Eschrichia coli isolated in samples following freezing (Schukken et al 1989).…”
Section: Discussionmentioning
confidence: 97%